BCAA Metabolism and Insulin Sensitivity – Dysregulated by Metabolic Status?. Issue 6 (27th February 2018) - Gannon, Nicholas P.; Schnuck, Jamie K.; Vaughan, Roger A.
Abstract: Branched‐chain amino acids (BCAAs) appear to influence several synthetic and catabolic cellular signaling cascades leading to altered phenotypes in mammals. BCAAs are most notably known to increase protein synthesis through modulating protein translation, explaining their appeal to resistance and endurance athletes for muscle hypertrophy, expedited recovery, and preservation of lean body mass. In addition to anabolic effects, BCAAs may increase mitochondrial content in skeletal muscle and adipocytes, possibly enhancing oxidative capacity. However, elevated circulating BCAA levels have been correlated with severity of insulin resistance. It is hypothesized that elevated circulating BCAAs observed in insulin resistance may result from dysregulated BCAA degradation. This review summarizes original reports that investigated the ability of BCAAs to alter glucose uptake in consequential cell types and experimental models. The review also discusses the interplay of BCAAs with other metabolic factors, and the role of excess lipid (and possibly energy excess) in the dysregulation of BCAA catabolism. Lastly, this article provides a working hypothesis of the mechanism(s) by which lipids may contribute to altered BCAA catabolism, which often accompanies metabolic disease. Abstract : Under conditions of energy homeostasis, branched‐chain amino acids (BCAAs) may promote improved metabolic phenotypes including improved glucose uptake/insulin sensitivity. Under conditions of chronic excess energy, cells (especially adipose) appear to lose the ability to degrade BCAAs, causing an accumulation of BCAAs and related metabolites in circulation. As with many metabolites during metabolic disease (such as lipids and glucose), BCAA accumulation appears to correlate and may have a predictive value of metabolic disease.